The effects of transfusion load on renal function in intraoperative salvage autotransfusion: a retrospective cohort study for 200 patients - Wang, Honglan; Zhang, Meixin; Gu, Yu; Zeng, Weixin; You, Mei; Chen, Wenxing; Wu, Zhongshu; Ye, Yahua; Yu, Weitao; Wang, Shuxuan; Zeng, Jingyang (Frontiers in Physiology, 2025)
ObjectivesThis study aimed to investigate the effect of transfusion load on renal function during intraoperative salvage auto-transfusion.MethodsA total of 200 patients were assigned to five groups based on the transfusion load: 0–200 mL (Group A, n = 40), 201–400 mL (Group B, n = 40), 401–600 mL (Group C, n = 40), 601–800 mL (Group D, n = 40), >800 mL (Group E, n = 40). Serum creatinine (sCr) and free hemoglobin (FHb) concentrations were measured at preoperative baseline (T0), 1 h (T3), 2 h (T4), 12 h (T5), and 24 h (T6) post-auto-transfusion. FHb and sCr levels were also assessed in the blood storage tank before washed (T1) and in the reinfusion bag after washing (T2).ResultsIn Groups A, B, and C, there was no significant change in sCr levels between T0 and subsequent time points (T3, T4, T5, T6). However, in Groups D and E, sCr levels increased by more than 26.5 μmol/L from baseline at T3 and T4, with sustained elevations at T3, T4, and T5 compared to T0. FHb concentrations were higher in both T1 and T2 compared to T0, following a similar trend as sCr. Patients receiving more than 600 mL of autologous transfusion showed a transient increase in sCr at 1 and 2 h post-transfusion, consistent with acute kidney injury (AKI), which resolved by 24 h after transfusion.ConclusionAttention should be paid to renal function in patients receiving large volumes (>600 mL) of salvaged blood during intraoperative auto-transfusion, as these patients may experience transient AKI, which resolves over time.